Integrating Sports in Ideological and Political Theory Courses: A Practical Approach for Enhancing Mental Health in Universities - Gaowei Dong, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In order to understand the practical teaching research of integrating ideological and political courses into sports in universities, practical teaching research of integrating ideological and political courses into sports in universities from the perspective of mental health has been proposed. This survey questionnaire sampled 10000 undergraduate students from a certain provincial university of science and technology. Through the questionnaire star system, counselors from 15 secondary colleges of the university distributed the questionnaire to each class in the 2019, 2020, 2011, and 2012 levels of their respective colleges. The survey questionnaire collected a total of 8000 valid questionnaires covering 15 colleges and four grades of the school. The results indicate that through questionnaire survey analysis and visits, it has been found that integrating ideological and political elements into college students' mental health education courses is an important way to strengthen the construction of college students' psychological capital and improve their ability to educate students in mental health education. The ideological and political education work for college students is an important component of helping them successfully complete their studies and grow healthily. It is an important measure to build a harmonious campus and an important guarantee for the comprehensive implementation of quality education.